FORMATION OF THE DAGESTAN INTELLIGENTSIA IN G.S.KAYMARAZOV’S WORKS - Zul'pukarova, El'mira Magomed-Gereevna (History, Archeology and Ethnography of the Caucasus, 2019)
Abstract. The article analyzes the works of Professor G.S. Kaymarazov, dedicated to the problem of the formation and development of the Dagestan intelligentsia. This problem is highly relevant, since the Dagestan intelligentsia, the formation of which began after the annexation of Dagestan to Russia, made a great contribution to the socio-economic and cultural development of the peoples of Dagestan. The relevance of this problem has increased recently, since some researchers have distortedly interpreted the role of the Russian intelligentsia in training intellectuals from Dagestan, as well as the contribution of Russian specialists to the economic and cultural development of Dagestan in the Soviet period. The article deals with the monographs of Professor G.S. Kaymarazov, published in different years, shows what aspects of the formation and development of the Dagestan intelligentsia he studied. The author of the article concludes that the works of G.S. Kaymarazov made a significant contribution to the study of the culture of the peoples of Dagestan, including the formation and development of the Dagestan intelligentsia.